ANALISIS KINERJA KEUANGAN PEMERINTAH KABUPATEN GORONTALO - Lantowa, Felmi D; yahya, Ismail Wirsan (JSAP : Journal Syariah and Accounting Public, 2023)
In the era of regional autonomy, they were given authority and responsibility in managing financial resources to ensure the prosperity of their people. One of the changes to the regional financial management system is the utilization of the Financial Accounting Information System. So it is very important for local governments to pay great attention to the performance of regional financial management. The purpose of this study is to determine the financial performance of the Gorontalo district government. The results of the study show that regional financial performance ratios in Gorontalo Regency during the 2017 – 2021 period show that all financial ratios have decreased from 2017 to 2020. Then in 2021 there will be improvements in terms of increasing financial performance when viewed from various financial ratios. So that the Gorontalo Regency Government must be able to maximize the potential that exists in the region to be able to improve financial performance which is generally lower than in 2017